2018
DOI: 10.1063/1.5049430
|View full text |Cite
|
Sign up to set email alerts
|

Molecular admixtures and impurities in atmospheric pressure plasma jets

Abstract: A more complete understanding of reactive chemistry generated by atmospheric pressure plasma jets (APPJs) is critical to many emerging medical, agricultural, and water treatment applications. Adding molecular gases to the noble working gas which flows through the jet is a common method to tailor the resulting production of reactive oxygen and nitrogen species (RONS). In this paper, results are discussed from a computational investigation of the consequences of H 2 O and O 2 admixtures on the reactive chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…A change in intensity reflects an underlying change in the electron energy distribution which is responsible for excitation processes. A low concentration molecular admixture into a rare gas significantly changes the electron energy distribution by introducing additional inelastic low energy processes including the excitation of low lying (< 0.1 eV) vibrational and rotational states [23]. An increase in gas temperature is not uncommon with molecular admixtures [24].…”
Section: Discussionmentioning
confidence: 99%
“…A change in intensity reflects an underlying change in the electron energy distribution which is responsible for excitation processes. A low concentration molecular admixture into a rare gas significantly changes the electron energy distribution by introducing additional inelastic low energy processes including the excitation of low lying (< 0.1 eV) vibrational and rotational states [23]. An increase in gas temperature is not uncommon with molecular admixtures [24].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the TDD efficiency of the plasma jet array improved significantly when the 0.5% O 2 is mixed with the working gas, which is related to more ROS generated by the plasma, as reports indicated that the density of the ROS generated by the plasma increase when some oxygen is mixed into the working gas. [32][33][34][35] As the applied voltage increased to 9 kV 9 kHz, compared with 7 kV 7 kHz group, the TDD efficiency was not changed significantly after 3 min treatment, while 6 min treatment increased significantly, which shows that the plasma jet has a cumulative effect on enhancing TDD efficiency. The mixing of O 2 still plays an important role so that the efficiency of 6 min 7 kV 7 kHz He/O 2 mixture group is higher than 6 min 9 kV 9 kHz pure helium group.…”
Section: Patent Blue V Tdd Testmentioning
confidence: 92%
“…For example the electric field can cause electroporation of cell membranes, allowing molecules (including ROS and RNS) to enter the cells and cause damage to the cell's internal organelles (including mitochondria) and macromolecules such as lipids, proteins, and DNA. To learn more about the physics and design of LTP sources the reader is referred to the following references [23,27,[54][55][56][57].…”
Section: Non-equilibrium Atmospheric Pressure Plasma Jets (N-appj)mentioning
confidence: 99%